2013
DOI: 10.5194/bg-10-871-2013
|View full text |Cite
|
Sign up to set email alerts
|

Isoprene emissions from a tundra ecosystem

Abstract: Whole-system fluxes of isoprene from a moist acidic tundra ecosystem and leaf-level emission rates of isoprene from a common species (<i>Salix pulchra</i>) in that same ecosystem were measured during three separate field campaigns. The field campaigns were conducted during the summers of 2005, 2010 and 2011 and took place at the Toolik Field Station (68.6&deg; N, 149.6&deg; W) on the north slope of the Brooks Range in Alaska, USA. The maximum rate of whole-system isoprene flux measured was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 126 publications
5
57
2
Order By: Relevance
“…However, some earlier measurements show abundant isoprene concentration over Alaskan boreal forests (Blake et al, ). Isoprene fluxes in tundra systems have also been measured in Greenland (Kramshoj et al, ; Lindwall et al, ; Schollert et al, ; Vedel‐Petersen et al, ), northern Sweden (Faubert et al, ; Tang et al, ), and the Alaskan North Slope (Potosnak et al, ). All of these measurements show a very strong positive temperature dependence of isoprene fluxes, likely due to the higher emission potentials for isoprenoids in tundra vegetation than in temperate species (Rinnan et al, ).…”
Section: Local Arctic Air Pollutant Emissionsmentioning
confidence: 99%
“…However, some earlier measurements show abundant isoprene concentration over Alaskan boreal forests (Blake et al, ). Isoprene fluxes in tundra systems have also been measured in Greenland (Kramshoj et al, ; Lindwall et al, ; Schollert et al, ; Vedel‐Petersen et al, ), northern Sweden (Faubert et al, ; Tang et al, ), and the Alaskan North Slope (Potosnak et al, ). All of these measurements show a very strong positive temperature dependence of isoprene fluxes, likely due to the higher emission potentials for isoprenoids in tundra vegetation than in temperate species (Rinnan et al, ).…”
Section: Local Arctic Air Pollutant Emissionsmentioning
confidence: 99%
“…In subarctic and Arctic regions, the rate of increase in air temperature is predicted to be as much as twice the global average (IPCC, ), and this highlights the importance of gaining knowledge about BVOCs emitted from plant communities in these regions. Northern ecosystems from subarctic/Arctic wetlands (Faubert, Tiiva, Rinnan, Räsänen, et al, ; Holst et al, ) to heath tundra (Faubert, Tiiva, Rinnan, Michelsen, et al, ; Potosnak et al, ; Schollert et al, ; Tiiva et al, ) have shown significant BVOC emissions. The field experiments mimicking warmer climate have shown a great potential of increase in BVOC emissions from these ecosystems in response to different time spans of moderate warming (Faubert, Tiiva, Rinnan, Michelsen, et al, ; Kramshøj et al, ; Lindwall, Schollert, et al, ; Lindwall, Svendsen, et al, ; Tiiva et al, ; Valolahti et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…1) under standard conditions. The crop and tundra PFTs are non-emitting for isoprene in this model although recently, isoprene emission has been observed from a tundra ecosystem (Potosnak et al, 2013). Deciduous, shrub and rainforest PFTs maintain the highest fraction of electrons available for isoprene synthesis (Table 1).…”
Section: Leaf Isoprene Productionmentioning
confidence: 97%